Questionnaire-based risk assessment for amoebic gill disease (AGD) and evaluation of freshwater bathing efficacy of reared Atlantic salmon Salmo salar - Douglas-Helders, GM; Saksida, S; Barbara Nowak (2005)
Factors causing amoebic gill disease (AGD), the main disease affecting the salmonid industry in Tasmania, are largely unknown. Managers of 57 sites, from 4 countries, in both the Southern and Northern Hemisphere were questioned regarding the 2000 smolt year-class Atlantic salmon. Questions included site characteristics, fish population characteristics, husbandry and management programs, through to freshwater bathing characteristics. Possible risk factors for AGD outbreaks that were identified in this study using farm managers' opinions were mixed sex stocks (Tasmania), downstream positioning from other salmonid farming sites (pooled), tidal sites (Tasmania), depth of site (pooled), rate of salinity change in halocline and depth of halocline (pooled, Tasmania), phytoplankton blooms (pooled, Tasmania), antifouling paints (Tasmania, overseas) and automated feeding (pooled, overseas). The information from farm managers suggested that freshwater bathing is less effective with smaller bathing cages and lower levels of saturated oxygen in the bathing water. Risk factors could not always be determined due to the complex interactions between the biological and chemical environment, host and pathogenic factors, coupled with low sample numbers. Â© Inter-Research 2005.